Numerical investigation of aircraft wake vortex decay using large eddy simulations - Lakkam, Sreetej (2016)
This work presents a comprehensive study of aircraft wake vortex decay analysis in ground proximity using Large Eddy Simulation (LES). An in-house FORTRAN code named Jetcode was used to analyze the vortex decay parameters. Parametric investigations were performed on three different mesh configurations and using various periodic perturbation functions on single vortex flows for estimation and reduction of simulation time and computation resources requirements. Perturbations were introduced into the vortex flows to accelerate the vortex decay process and periodic functions were used to systematically initiate flow turbulence, which is generally known for its chaotic origins. Appreciable parameter combinations were applied to counter rotating aircraft wake vortex model to investigate the vortex decay characteristics in the wake flow. Several vortex characteristics like circulation strength, vortex center displacement, lateral and vertical movement of the vortex and vortex core radius variation were analyzed. In order to understand the applicability of Sub Grid Scale (SGS) models to the vortex flow analysis detailed studies of Smagorinsky and Dynamic Smagorinsky models were performed. The effectiveness of the SGS models to compute the energy transfer between the grid scales and sub grid scales was visualized by analyzing the eddy viscosity dissipation among the scales of motion for different flow conditions. Beside the investigation of wake vortex decay acceleration, the study also aims at optimizing the mesh resolution required for vortex flow analysis in the ground proximity.